Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13018-020-02074-x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral-dominant reduction in muscle volume in female knee osteoarthritis patients: computed tomography-based analysis of bilateral sides

Abstract: Background Muscle weakness is associated with osteoarthritis pathology. A recent study demonstrated that measuring muscle volume using computed tomography (CT)-based analysis and comparing bilateral muscles in the same patient allowed for accurate evaluation of muscle volume in unilateral hip osteoarthritis (OA) patients. Here, we evaluated muscle volume using CT-based analysis and compared bilateral muscles in knee OA (KOA) patients. Methods CT images were obtained from 35 female radiographic KOA patients th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…At the same time, it can be predicted that exercising in the face of pain or joint swelling, or failing to exercise entirely, can be expected to set the stage for muscle atrophy [37,38], as well as a decline in muscle strength and volume loss [39,40] and multiple functional aberrations that worsen over time.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it can be predicted that exercising in the face of pain or joint swelling, or failing to exercise entirely, can be expected to set the stage for muscle atrophy [37,38], as well as a decline in muscle strength and volume loss [39,40] and multiple functional aberrations that worsen over time.…”
Section: Resultsmentioning
confidence: 99%
“…In BG, only the difference in the thickness of the VM between the two lower limbs was not significant, but the thickness of RF, VM, and VL was higher in RML. There was a significant reduction of QF thickness in RSL relative to RML, which may be related to more severe long-term pain, functional limitation, and load reduction ( Tsukada et al, 2020 ). Several previous studies in human have suggested unilateral mechanical loading as a possible cause of muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetry between the lower limbs seems to be more prevalent in individuals with B-KO 5 , while the reduction in muscle strength and volume of the affected limb is more observed in individuals with U-KO 6 , and both (B-KO and U-KO) have already been associated with primary and secondary hyperalgesia 7 . However, these clinical differences have been less investigated.…”
Section: Introductionmentioning
confidence: 99%